The Impact of Lowering Carbon Emissions on Corporate Labour Investment: A Quasi-Natural Experiment - Cao, June; Li, W.; Hasan, I. (Elsevier, 2023)
We examine the impact of low-carbon city (LCC) initiatives on labour investment decisions (quantity, quality, and well-being). Using a time-varying difference-in-differences approach based on staggered implementations of such a pilot program, we report an inefficient outcome - absolute deviation of labour investment from the optimal net hiring – especially for firms in labour-intensive industries and firms with high financial slack or adjustment costs. We, however, observe increased investments in highly skilled personnel and compensated with employee stock ownership, especially by firms under intense pressure to reduce carbon emissions. Such initiatives are also closely associated with the significant enhancement of workplace safety. Overall, LCC helps to upgrade the corporate labour structure by hiring more skilled employees through reduced agency problems and heightened green innovation.